1988
DOI: 10.1177/0148607188012002185
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic‐Lock Technique: A New Approach to Optimal Therapy for Catheter‐Related Sepsis in Home‐Parenteral Nutrition Patients

Abstract: During a cumulated survey of 286 months, covering 11 gastroenterological patients under nocturnal-cyclic home parenteral nutrition, 24 cases of catheter-related sepsis were observed (one/11.9 months). None of these were associated with focus of infection at the cutaneous entry point or at the subcutaneous tunnel of the catheters. In this study attempt was made to control sepsis without removal of the surgically implanted siliconed lines (Vygon code 180-20 with an internal filling volume of 1 ml). The first two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
133
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(140 citation statements)
references
References 17 publications
2
133
0
5
Order By: Relevance
“…56 Antimicrobial (taurolidine) flush solutions and antibiotic lock techniques have been proposed for patients with recurrent CVC infections. 57,58 A recent randomised study of 30 patients found taurolidine lock to be highly effective in reducing subsequent CVC infection with a mean infection-free survival of 175 days compared with 641 days with the introduction of taurolidine locks (P ! 0.0001).…”
Section: Complications Of Long-term Pnmentioning
confidence: 99%
“…56 Antimicrobial (taurolidine) flush solutions and antibiotic lock techniques have been proposed for patients with recurrent CVC infections. 57,58 A recent randomised study of 30 patients found taurolidine lock to be highly effective in reducing subsequent CVC infection with a mean infection-free survival of 175 days compared with 641 days with the introduction of taurolidine locks (P ! 0.0001).…”
Section: Complications Of Long-term Pnmentioning
confidence: 99%
“…More than 20 years ago, a new method for treating CRB in patients who received total parenteral nutrition [37] was first reported. This technique involves instilling a highly concentrated antimicrobial−anticoagulant solution at the end of a dialysis session which "locks" the catheter when it is not in use [38].…”
Section: Time For Preventing Recurrence Of Catheter-related Bacteremiamentioning
confidence: 99%
“…Several open trials of antibiotic lock therapy of tunneled catheter-related bacteremia, with or without concomitant parenteral therapy, have reported a response and catheter salvage without relapse in 138 (82.6%) of 167 episodes (Messing et al 1988;Capdevila et al 1993;Johnson et al 1994;Williams et al 1994;Benoit et al 1995;Krzywda et al 1995;Mermel et al 2001). Compared with parenteral therapy used in the aforementioned open trials, therapy including AL was significantly more likely to result in catheter salvage.…”
Section: Discussionmentioning
confidence: 99%